2009
DOI: 10.1111/j.1463-5224.2008.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary plasmacytoma of the third eyelid gland in a dog

Abstract: A case of extramedullary plasmacytoma of the third eyelid gland in a 7-year-old American Cocker Spaniel is reported. An enlargement of the third eyelid gland, abundant mucopurulent discharge, mild hyperemia and corneal pigmentation in the OD was present. Excisional biopsy of the mass revealed the gland was infiltrated and partially destroyed by a uniform population of neoplastic plasma cells. The neoplastic cells were positive for CD138, Ki-67 and lambda light chain. CD20, CD3, kappa light chain and cytokerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 16 publications
1
30
1
1
Order By: Relevance
“…The characteristics of dog plasma cells are the domination of lambda light chains (7). Both histopathological and immunohistochemical findings for our patient's tumor were in concordance with previous data.…”
Section: Resultssupporting
confidence: 79%
“…The characteristics of dog plasma cells are the domination of lambda light chains (7). Both histopathological and immunohistochemical findings for our patient's tumor were in concordance with previous data.…”
Section: Resultssupporting
confidence: 79%
“…One year after surgery, there was no recurrence of the tumour and the tumour on the other side was reported to be of similar size to when it was first discovered. The third eyelid plasmacytoma case reported by Perlmann et al (2009), also exhibited no recurrence one year after resection of the tumour only, as they managed to complete the resection while preserving the third eyelid. Mucosa-associated lymphoid tissue lymphoma is known to generally develop only locally where it first developed and to not spread to other sites (Coupland et al 2002).…”
Section: Discussionmentioning
confidence: 94%
“…On rare occasions, a primary tumour can develop within these cells (Ota-Kuroki et al 2014). Perlmann et al (2009) reported a case of an extramedullary plasmacytoma in a 7-year-old American cocker spaniel. Hong et al (2011) reported a case of a mucosa-associated lymphoid tissue (MALT) lymphoma also in a 4-year-old Cocker spaniel.…”
mentioning
confidence: 99%
“…However, routine immunohistochemistry techniques are not expected to differentiate plasmacytomas and B-cell lymphomas in dogs; these tumours are distinguishable by light microscopy and clinical features (Baer et al 1989;Fernandez et al 2005;Perlmann et al 2009). Adjunctive cytology would have been useful in this case to help assess plasma cell morphology.…”
Section: Discussionmentioning
confidence: 96%
“…Surgical resection is less likely to be complete with alimentary plasmacytomas and multiple lesions have been reported (Kupanoff et al 2006). Other rare sites of extramedullary plasmacytomas include the spleen, genitalia, eye, third eyelid, uterus and liver (Rakich et al 1989;Clark et al 1992;Perlmann et al 2009). …”
Section: Introductionmentioning
confidence: 96%